Time and frequency domain models for multiaxial fatigue life estimation under random loading - Andrea Carpinteri; Andrea Spagnoli; Camilla Ronchei; Sabrina Vantadori (Fracture and Structural Integrity)
Engineering structures and components are often subjected to random fatigue loading produced, for example, by wind turbulences, marine waves and vibrations. The methods available in the literature for fatigue assessment under random loading are formulated in time domain or, alternatively, in frequency domain. The former methods require the knowledge of the loading time history, and a large number of experimental tests/numerical simulations is needed to obtain statistically reliable results. The latter methods are generally more advantageous with respect to the time domain ones, allowing a rapid fatigue damage evaluation. In the present paper, a multiaxial criterion formulated in the frequency-domain is presented to estimate the fatigue lives of smooth metallic structures subjected to combined bending and torsion random loading. A comparison in terms of fatigue life prediction by employing a time domain methods, previously proposed by the authors, is also performed.